A target-oriented performance assessment and model development of a grid-connected solar PV (GCPV) system for a commercial building in Malaysia. (June 2021) - Saleheen, Mohammed Zeehan; Salema, Arshad Adam; Mominul Islam, Shah Mohammad; Sarimuthu, Charles R.; Hasan, Md Zobaer
Abstract: This paper presents a detailed target-oriented performance assessment of a 232.5 kWp grid-connected solar PV (GCPV) system installed on a commercial building in Malaysia. Technical and meteorological data for 2019, in 5-min intervals, was retrieved from the solar data logger. The GCPV system generated about 301.5 MWh of energy in 2019, almost achieving the stated target of 305.0 MWh. While most months in 2019 successfully achieved the set monthly target, some did not due to low solar irradiance. The Performance Ratio (PR), Capacity Utilization Factor (CUF), system efficiency, and Levelized Cost of Energy (LCOE) were found to be 85.4%, 14.85%, 9.15%, and 0.396 MYR/kWh, respectively. The PR of the present GCPV system was higher than other GCPV systems surveyed. Approximately 177 metric tons of CO2 emissions were saved during the year after installing the GCPV system. In addition, performance models, based on the key factors of solar irradiation and PV module temperature that affect the yield and power output of the GCPV system, were developed and tested statistically. The findings of this study should be of use to solar energy customers and stakeholders. Graphical abstract: Image 1 Highlights: A target-oriented performance analysis of grid-connected solar PV (GCPV) system is assessed. Actual yield of GCPV system achieved about 90% of the set target yield. The annual PR, CUF, and system efficiency was 85.4%, 14.85%, and 9.15%, respectively. The payback period and LCOE was ∼8 years and 0.396 MYR/kWh, respectively. About 177 metric tons of CO2 was reduced due to GCPV system.